PHYSICAL MASS TRANSFER MODEL AND SCALE-UP DESIGN PROCEDURE FOR AEROBIC BIOREACTORS - Nawaz, Z.; Sheikh, N. A.; Khan, J. R. (The Nucleus, 2020)
The scale-up design procedure based on new physical mass transfer model aerobic bioreactors is developed. This scale-up procedure can be used to determine the disc surface area needed to prevent an oxygen limitation or to obtain a specific degree of treatment. In contrast to the empirical and earliest rotating biological contactors performance model, a major advantage of the physical mass transfer model design is the prediction of the onset of oxygen limiting conditions since it accounts for the fact that low dissolved oxygen concentrations can limit the growth rate of the attached microorganisms.